Estrategia de marketing digital en el Comercial Reyna del Cisne en el cantón Simón Bolívar provincia del Guayas, periodo 2024. - Valenzuela Alvarado, John Alexander (2025)
This case study, titled "DIGITAL MARKETING STRATEGY FOR COMERCIAL REYNA DEL CISNE IN SIMÓN BOLÍVAR CANTON, GUAYAS PROVINCE, 2024 PERIOD," falls within the research line of Financial and Administrative Management, linked to the subline of Marketing and Commercialization. The main objective is to analyze digital marketing strategies that optimize digital presence and enhance competitiveness in the local market. The study focuses on analyzing the current situation of the business, identifying the impact of not having digital tools. Through interviews with the owner and surveys of customers, it was determined that most consumers prefer to receive information about products and promotions through digital platforms, as well as their interest in making online purchases. Additionally, there is a need to train staff in the use of digital tools to improve customer interaction and optimize sales processes. The applied methodology included a descriptive and analytical approach, which allowed for detailed information on customer preferences and the business's weaknesses in the digital realm. As a result, comprehensive digital strategies are proposed, such as scheduling social media posts and implementing an online sales platform. These actions aim to modernize commercial practices, increase business visibility, and foster customer loyalty, adapting to current market trends.